Modelling the brittle failure of graphite induced by the controlled impact of runaway electrons in DIII-D - S. Ratynskaia; P. Tolias; T. Rizzi; K. Paschalidis; A. Kulachenko; E. Hollmann; M. Beidler; Y. Liu; D. Rudakov; I. Bykov; R.A. Pitts (Nuclear Fusion)
The thermo-mechanical response of an ATJ graphite sample to controlled runaway electron (RE) dissipation, realized in DIII-D, is modelled with a novel work-flow that features the RE orbit code KORC, the Monte Carlo particle transport code Geant4 and the finite element multiphysics software COMSOL. KORC provides the RE striking positions and momenta, Geant4 calculates the volumetric energy deposition and COMSOL simulates the thermoelastic response. Brittle failure is predicted according to the maximum normal stress criterion, which is suitable for ATJ graphite owing to its linear elastic behavior up to fracture and its isotropic mechanical properties. Measurements of the conducted energy, damage topology, explosion timing and blown-off material volume, impose a number of empirical constraints that suffice to distinguish between different RE impact scenarios and to identify RE parameters which provide the best match to the observations.